Phenolic and Flavonoid Responses of Bauji Shallots to Ammonium Sulfate under Floating Cultivation - Hidayanti, Syafira Zulfa; Susilawati, Susilawati; Suwandi, Suwandi (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Shallot is a high value horticultural crop valued for its flavor, aroma, and medicinal properties, and is rich in phenolics and flavonoids that contribute to antioxidant activity. Limited dryland and fluctuating demand in South Sumatra highlight the need for alternative systems such as floating cultivation. This study aimed to evaluate the effects of different ammonium sulfate (ZA) doses on the bulb yield, total phenolic, and flavonoid contents of Bauji shallots grown under floating cultivation. The experiment used a randomized complete block design with three replications and four ZA fertilizer treatments (0, 60, 180, and 360 kg ha⁻¹). Observed variables included total phenolic and flavonoid contents measured by spectrophotometry and dry bulb weight. The results indicated that the ZA application significantly increased dry bulb weight and total phenolic content but did not affect flavonoids. The highest bulb yield and flavonoid content were obtained with 60 kg ha⁻¹, whereas phenolics peaked under the control (0 kg ha⁻¹), suggesting a trade-off between yield and secondary metabolite accumulation. Correlation analysis revealed a positive association between bulb weight and flavonoid content, whereas phenolics were negatively related to fertilizer input. As the first report on Bauji shallots under floating cultivation, these findings indicate that moderate ZA fertilization (60 kg ha⁻¹) optimizes bulb yield while maintaining bioactive compound levels. However, further multi-season studies are needed for broader recommendations.